Answer

Verified

450k+ views

Hint: Let's make use of the formula \[{n_{{C_r} = \dfrac{{n!}}{{(n - r)!r!}}}}\] \[\] and solve this.

Complete step-by-step answer:

By making use of the formula \[{n_{{C_r} = \dfrac{{n!}}{{(n - r)!r!}}}}\]

We can write \[{n_{{C_6} = \dfrac{{n!}}{{(n - 6)!6!}}}}\]

\[n - {3_{{C_3} = \dfrac{{n!}}{{(n - 6)!3!}}}}\]

So ,now we can write the ratio $\dfrac{{^n{C_6}}}{{^{n - 3}{C_3}}} = \dfrac{{33}}{4}$

Lets substitute the values of $^n{C_6}$ and $^n{C_3}$

So, we get \[\dfrac{{_{\dfrac{{n!}}{{(n - 6)!6!}}}}}{{_{\dfrac{{(n - 3)!}}{{(n - 6)!3!}}}}} = \dfrac{{33}}{4}\]

Here, we will make use of the formula $n! = n(n - 1)!$ and write

$n! = n(n - 1)(n - 2)(n - 3)!$ in the numerator .

So, from this we can cancel out $(n - 3)!,(n - 6)!$ in the numerator and denominator

$\dfrac{{n(n - 1)(n - 2)}}{{6!}} \times 3! = \dfrac{{33}}{4}$

On shifting $6!$ and $3!$ to the right hand side, we get

$n(n - 1)(n - 2) = 11 \times 3 \times 5 \times 2 \times 3 = 11 \times 10 \times 9$

Therefore n=11.

Note: While expressing $n! = n(n - 1)!$ express it upto the term which is present in the denominator so that the terms in the numerator and denominator will get cancelled out and it would be easy to solve.

Complete step-by-step answer:

By making use of the formula \[{n_{{C_r} = \dfrac{{n!}}{{(n - r)!r!}}}}\]

We can write \[{n_{{C_6} = \dfrac{{n!}}{{(n - 6)!6!}}}}\]

\[n - {3_{{C_3} = \dfrac{{n!}}{{(n - 6)!3!}}}}\]

So ,now we can write the ratio $\dfrac{{^n{C_6}}}{{^{n - 3}{C_3}}} = \dfrac{{33}}{4}$

Lets substitute the values of $^n{C_6}$ and $^n{C_3}$

So, we get \[\dfrac{{_{\dfrac{{n!}}{{(n - 6)!6!}}}}}{{_{\dfrac{{(n - 3)!}}{{(n - 6)!3!}}}}} = \dfrac{{33}}{4}\]

Here, we will make use of the formula $n! = n(n - 1)!$ and write

$n! = n(n - 1)(n - 2)(n - 3)!$ in the numerator .

So, from this we can cancel out $(n - 3)!,(n - 6)!$ in the numerator and denominator

$\dfrac{{n(n - 1)(n - 2)}}{{6!}} \times 3! = \dfrac{{33}}{4}$

On shifting $6!$ and $3!$ to the right hand side, we get

$n(n - 1)(n - 2) = 11 \times 3 \times 5 \times 2 \times 3 = 11 \times 10 \times 9$

Therefore n=11.

Note: While expressing $n! = n(n - 1)!$ express it upto the term which is present in the denominator so that the terms in the numerator and denominator will get cancelled out and it would be easy to solve.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE